P36 The role of EGFR pathway activation in sinonasal carcinoma. Issue 5 (May 2015) - , .; García-Inclán, C.; Costales, M.; López-Hernández, A.; Vivanco, B.; Llorente, J.L.; Hermsen, M.
Abstract : Introduction: Two major tumour types exist in the sinonasal cavities: squamous cell carcinomas (SNSCC) and intestinal-type adenocarcinoma (ITAC). Both are etiologically related to several occupational exposure, especially wood and leather dust. Despite improvements in the field of surgery and radiotherapy, patients with these tumours still face a very unfavorable prognosis and new therapeutic approaches are needed. Previous studies indicated that EGFR is overexpressed in approximately 40% of cases and KRAS and BRAF mutations are rare, suggesting that targeted anti-EGFR therapy with monoclonal antibodies may be effective. The aim of this study was to further examine downstream factors in the EGFR pathway in these tumours. Material and methods: Protein expression of PTEN, pAKT and mTOR was analysed by immunohistochemistry using tissue microarrays containing primary tumours of 54 SNSCC and 98 ITAC. Results were correlated to clinico-pathological characteristics and follow-up data, as well as to the previously obtained results on EGFR, KRAS and BRAF. Results: Loss of expression of PTEN was found in 30% of all tumours, irrespective of EGFR expression status. Co-expression of pAKT and mTOR was significantly more frequent in ITAC (40%) than in SNSCC (10%) and did not correlate to any of the clinical parameters. Conclusions: The analysis of downstream factors in the EGFR pathway may help to predict therapeutic response. Anti-EGFR targeted therapy may be useful for a subset of patients with sinonasal carcinoma, particularly those that demonstrate EGFR overexpression and normal expression of PTEN. The finding of activated pAKT and mTOR in ITAC may open the possibility for anticancer therapy with inhibitors such as rapamycin.